Frequency and Risk Factors of Seizures in Children During Induction Remission Chemotherapy for Acute Lymphoblastic Leukemia (ALL) (Bangladesh Journal of Child Health, 2022)
Background: Seizure is one of the most common CNS complications among patients receiving chemotherapy for acute lymphoblastic leukemia (ALL). Seizures are seen in 8-13% of patients with ALL. Most seizure occurs during the induction and consolidation phases of treatment. However, not much is known about the risk factors of these seizure.Materials & Method: This prospective observational study was conducted in the department of Pediatric Hematology and Oncology, BSMMU. One hundred and five newly diagnosed admitted children with ALL aged >1 year to